Interplay of Biochemical, Genetic, and Immunohistochemical Factors in the Etio-Pathogenesis of Gastric Ulcer in Rats: A Comparative Study of the Effect of Pomegranate Loaded Nanoparticles Versus Pomegranate Peel Extract - Abd el-Rady, Nessren M.; Dahpy, Marwa A.; Ahmed, Amel; Elgamal, Dalia A.; Hadiya, Safy; Ahmed, Mai A. M.; Sayed, Zain El-Abdeen Ahmed; Abdeltawab, Doaa; Abdelmohsen, Ahmed Shawkat; Farrag, Alshaimaa Abdelkhaliq Mohammad; Ashmawy, Ahmed M.; Khairallah, Marwa K.; et al. (Frontiers in Physiology, 2021)
Background: Nanotechnology is a recent area of research in several modalities of life as medicine, engineering and cosmetics. Few data are available about the role of herbal extract loaded nanoparticles as an alternative safe medicine for management of gastric ulcer. Aim: this work was targeted to explore the physiological effects of pomegranate loaded nanoparticles (PLN) against indomethacin IND-induced gastric ulcer and comparing the results with the traditional pomegranate peel extract (PPE). Methods: 24 rats were equally distributed into 4 groups: control, IND-treated, PLN-treated and PPE-treated groups. Gross examination of gastric mucosa, calculation of ulcer and inhibition indices was done. Serum malondialdehyde (MDA), total antioxidant capacity (TAC), interleukin 2 (IL-2), IL-6, IL-10, gastric prostaglandin E2 (PGE2) and nitric oxide (NO) were estimated. Mucosal endothelial nitric oxide synthase (eNOS-mRNA) was identified by qPCR. General histological, immuno-histochemical staining of Tumor necrosis factor-α (TNF-α) and eNOS of stomach mucosa were performed. Results: In comparison with the control group, IND-treated rats showed visible multiple ulcers with ulcer index, serum MDA, IL-2 & IL-6 were elevated while IL-10, PGE2, NO, eNOS mRNA were reduced significantly. Damaged surface epithelium with disrupted glandular architecture and heavy leucocyte infiltration of lamina propria was noticed. Immunohistochemical staining of stomach mucosa revealed marked increased TNF-α and reduced eNOS. Oral administration of PLN and PPE succeeded in improving gross mucosal picture, all biochemical, histological, immunohistochemical alterations. However, the healing effect of PLN was obviously greater than PPE-treated rats. Conclusion: both PLN and PPE potently alleviated IND-gastric ulceration via increasing TAC, PGE¬2, NO, eNOS mRNA and protein expression.